Seismic Anisotropy in Subduction Zones: Evaluating the Role of Chloritoid - Lee, Jungjin; Mookherjee, Mainak; Kim, Taehwan; Jung, Haemyeong; Klemd, Reiner (Frontiers in Earth Science, 2021)
Subduction zones are often characterized by the presence of strong trench-parallel seismic anisotropy and large delay times. Hydrous minerals, owing to their large elastic anisotropy and strong lattice preferred orientations (LPOs) are often invoked to explain these observations. However, the elasticity and the LPO of chloritoid, which is one of such hydrous phases relevant in subduction zone settings, is poorly understood. In this study, we measured the LPO of polycrystalline chloritoid in natural rock samples, obtained the LPO-induced seismic anisotropy, and evaluated the thermodynamic stability field of chloritoid in subduction zones. The LPO of chloritoid aggregates displayed a strong alignment of the [001] axes subnormal to the rock foliation, with a girdle distribution of the [100] axes and the (010) pol es subparallel to the foliation. New elasticity data of single-crystal chloritoid showed a strong elastic anisotropy of chloritoid with 47% for S-waves (VS) and 22% for P-waves (VP), respectively. The combination of the LPO and the elastic anisotropy of the chloritoid aggregates produced a strong S-wave anisotropy with a maximum AVS of 18% and a P-wave anisotropy with an AVP of 10%. The role of chloritoid LPO in seismic anisotropy was evaluated in natural rock samples and a hypothetical blueschist. Our results indicate that the strong LPO of chloritoid along the subduction interface and in subducting slabs can influence the trench-parallel seismic anisotropy in subduction zones with “cold” geotherms.